FEATURES OF THE STUDY OF THE ISSUES OF NATIONAL IDENTITY OF UZBEKS IN SOVIET HISTORIOGRAPHY (Scientific journal of the Fergana State University, 2023)
This article analyzes the problem of covering the ethnic identity of Uzbeks in the Soviet period from the point of view of historiography. According to the author, the researchers of the Soviet era, although they did not directly study the issues of ethnic identity of Uzbeks, but described the processes of ethnogenesis, ethnic history, ethnicity and national consolidation of the Uzbek people, which was elucidated. In addition, at this time rich ethnographic materials on Uzbek ethnography were collected, and today there is an opportunity to study them on the basis of the concept of identity